Fauna Fantasi Educational Game for Improving English Animal Vocabulary - Nazar, Muhammad; Lutfi, Fauzi (Gameology and Multimedia Expert, 2025)
This paper presents Fauna Fantasi, an educational game designed to support primary school children in learning English vocabulary through an interactive and enjoyable experience. Targeted at learners aged 6 to 12 years, the game integrates playful exploration with language development by challenging players to collect scattered letters that form English words. Featuring cheerful visuals, intuitive controls, and progressively challenging levels, Fauna Fantasi aims to maintain engagement while reinforcing new vocabulary. Early observations indicate that this approach successfully captures children’s interest and promotes vocabulary retention by embedding learning within an adventurous context. The game’s effectiveness can be further assessed through structured pre- and post-tests and by observing how well players identify and construct words during gameplay. Overall, Fauna Fantasi illustrates the potential of game-based learning as a meaningful tool to enhance English language acquisition among young students.